Problems of the Chinese revolution - Leon Trotsky ; with appendices by Zinoviev, Vuyovitch, Nassunov & others ; translated with an introd. by Max Shachtman. (Paragon Book Reprint Corp., 1962)
First printed in June 1932 by Pioneer Publishers, New York. "Glossary of Names and Terms: 16 p. at the end."